Upaya pencegahan infeksi oleh bidan praktik swasta dalam asuhan persallinan di Kabupaten Kulon Progo - Munica Rita Hernayanti; Martha Irene Kartasurya; Dharminto Dharminto (Poltekkes Kemenkes Yogyakarta, 2012)
Infection prevention practices by health workers was still selectively done. ln Kulon Progo district 44.4% of infant mortality was caused by sepsis, 9% by post-delivery fever complication. The majority of delivery assistance (59 %) was done by private Practice Midwife (BPS). Almost a half (47.8%) of BPS has Delima midwives predicate. They should do their work with service of excellence. A preliminary study showed that Delima midwives did not take into account infection prevention and they felt that infection prevention was annoying. The study objective was to identify infection preventive action difference between Delima and non Delima midwives in the delivery care. This was an observational analytic and comparative study with cross sectional approach. Study population was all 90 BPS in Kulon Progo district. Study subjects consist of 34 Delima midwives and 34 BPS non Delima who fulfilled inclusions and exclusion criteria. Data were collected through survey using questionnaire and observation using observation sheet. Results of study showed that Delima midwives had higher value on eight examined variables than non Delima BPS. Result of a difference test showed that there was a significant difference in the implementation of infection prevention (p = 0.003), knowledge (p = 0.037), attitude (p = 0.03), patient satisfaction perceptions (p = 0.016), perception on workload (p = 0.027), support from organization profession (p = 0.012). There was no significant difference in infection preventive training (p = 0.169) and midwives’ motivation (p = 0.325). Result of bivariate test with age stratification showed that two variables namely implementation of infection prevention and patient satisfaction perceptions were not significantly different in both elder age group and young age group. Recommendation for lBl is to establish standard procedure of infection prevention in the delivery care. All members of lBI should obey this standard procedure. lBl should develop Delima midwives’ program to improve BPS service. Recommendations for district health office are to facilitate training implementation on the management of infection prevention, to collaborate with IBI to do supervision to BPS focusing on important of infection prevention especially in the delivery care.